2011
DOI: 10.1007/s00436-011-2295-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of Trichobilharzia franki Müller and Kimmig, 1994 (Digenea: Schistosomatidae) in Radix auricularia from Central Italy

Abstract: The molecular approach was used to identify the first focus of human cercarial dermatitis occurring during the spring-summer season in Vico Lake, a Natural Reserve Area in Central Italy. Sequences of 586 bp length of the partial region of 18S and ITS-1 ribosomal DNA from cercariae were obtained. They were compared with extant GenBank sequences of Trichobilharzia. Accordingly, the ocellate furcocercariae were identified as belonging to the species Trichobilharzia franki Müller and Kimmig, 1994. Sequences of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…At present, in Europe, foci of swimmer's itch have been reported from Czech Republic (Kolářová, Horák, & Sitko, ), Switzerland (Chamot, Toscani, & Rougemont, ), Poland (Zbikowska, ), France (Jouet et al, ), the Netherlands (Schets, Lodder, Duynhoven, & Roda Husman, ), England (Lawton et al, ), Germany (Selbach et al, ) and Belgium (Caron et al, ). In Italy, it was first reported in the lake of Garda (northern Italy) in 1998 (Golo et al, ) and, more recently, in central Italy in the lake of Vico, where Cipriani et al () identified the species T. franki as the causative agent of the dermatitis and R. auricularia as its intermediate host. At present, these are the only reports of cercarial dermatitis from our country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, in Europe, foci of swimmer's itch have been reported from Czech Republic (Kolářová, Horák, & Sitko, ), Switzerland (Chamot, Toscani, & Rougemont, ), Poland (Zbikowska, ), France (Jouet et al, ), the Netherlands (Schets, Lodder, Duynhoven, & Roda Husman, ), England (Lawton et al, ), Germany (Selbach et al, ) and Belgium (Caron et al, ). In Italy, it was first reported in the lake of Garda (northern Italy) in 1998 (Golo et al, ) and, more recently, in central Italy in the lake of Vico, where Cipriani et al () identified the species T. franki as the causative agent of the dermatitis and R. auricularia as its intermediate host. At present, these are the only reports of cercarial dermatitis from our country.…”
Section: Introductionmentioning
confidence: 99%
“…As man is an accidental host of these parasites, cercariae (furcocercariae) are not able to mature in humans and usually are killed in derma. In Europe, as well as in most of temperate latitudes, the most important agents of swimmer itch belong to the genus Trichobilharzia (Horák et al, ), namely the four species Trichobilharzia franki , Trichobilharzia szidati , Trichobilharzia regenti and Trichobilharzia salmanticencis (Cipriani, Mattiucci, Paletti, Scialanca, & Nascetti, ; Soldánová et al, ). Trichobilharzia spp.…”
Section: Introductionmentioning
confidence: 99%
“…To date, little is known of the prevalence of dermatitis caused by Trichobilharzia spp, because of both a lack of coordination between epidemiological studies and analysis of parasite-fauna of fresh water, and of the absence of previous diffusion of this dermatitis in Central Europe. The highest diffusion has been reported in Northern Europe and in Central and Eastern United States (1,3,4).…”
mentioning
confidence: 99%
“…Lake Vico, located in the Tuscia province of Central Italy, is of volcanic origin and is . frequented in the summer period by several bathers, and several cases have been reported in literature of skin eruptions accompanied by intense itching caused by Trichobilharzia spp after bathing in this lake (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation